Performance of well known packet scheduling algorithms in the downlink 3GPP LTE system - Mohd Ramli, Huda Adibah; Basukala, Riyaj; Sandrasegaran, Kumbesan; Patachaianand, Rachod (2009)
This paper investigates the performance of well known packet scheduling algorithms developed for single carrier wireless systems from a real time video streaming perspective. The performance evaluation is conducted using the downlink third generation partnership project long term evolution (3GPP LTE) system as the simulation platform. This paper contributes to the identification of a suitable packet scheduling algorithm for use in the downlink 3GPP LTE system supporting video streaming services. Simulation results show that, in the downlink 3GPP LTE system supporting video streaming services, maximum-largest weighted delay first (M-LWDF) algorithm outperforms other packet scheduling algorithms by providing a higher system throughput, supporting a higher number of users and guaranteeing fairness at a satisfactory level.